Have you ever heard of a kangaroo bird? : fascinating facts about unusual birds - Brenner, Barbara (Coward, McCann & Geoghegan, 1980)
Presents facts about unusual birds including the brightly colored puffin, the California condor, and an accomplished builder, the bowerbird.